Hubungan Tingkat Kecemasan Dengan Mekanisme Koping Pada Pasien Pre Operasi Di RSUD Kota Tanjungpinang - Ferdinan Tarigan; Fitriany Suangga; Rizki Sari Utami (Journal Clinical Pharmacy and Pharmaceutical Science, 2025)
Surgery is a treatment that uses invasive methods by opening and exposing the part of the body to be treated. Based on national table data from the Ministry of Health of the Republic of Indonesia, surgical procedures are ranked 11th out of the first 50 dealing with disease patterns in hospitals throughout Indonesia. In the city of Tanjungpinang, based on program reports from hospitals, there were 7,440 surgical cases found. The highest was at the Raja Ahmad Tabib Regional General Hospital, which was 3,240, higher than the total number of surgical cases in other districts or cities in the Riau Islands. This research was conducted to determine the relationship between anxiety levels and the coping mechanisms of pre-operative patients at the Tanjungpinang City Regional Hospital. This research method uses quantitative descriptive with a cross sectional approach. The sample consisted of 67 respondents, samples were taken using the Accidental Sampling technique. Data were processed using the Spearman Rank test. Bivariate analysis results show that there is a relationship between coping mechanisms and anxiety levels with a p value of 0.000. There is a relationship between the level of anxiety and the coping mechanisms of pre-operative patients at the Tanjungpinang City Regional Hospital. Recommendation: Educational programs or intervention development can be carried out to reduce anxiety levels in preoperative patients.